Off to the best start: The importance of infant and young child feeding - Hodge, Judith (International Food Policy Research Institute, 2016)
IN RECENT YEARS, nutrition interventions have focused on the critical first 1,000 days of life (from pregnancy up to the child’s second birthday), a period which has been identified as a window of opportunity for preventing child morbidity and mortality and ensuring adequate growth. During this time, children have higher nutritional needs to support rapid growth and development; if these are not met (and supported by adequate care and access to health services), loss in linear growth is largely irreversible and the potential for intervention to promote catch-up growth later on is minimal.1 Optimum nutrition in the first 1,000 days is also important for preventing overweight. Evidence suggests that infants with growth faltering in early life, followed by rapid weight gain in later childhood, might be at increased risk of adult obesity and noncommunicable diseases (NCDs), such as cardiovascular disease and hypertension. 2 Strategies to improve infant and young child feeding (IYCF) are therefore a cornerstone for the child survival and development programs of many countries.